Improving the passenger queue conditions of North and Taft Avenue stations of Metro Rail Transit 3 - Macaraig, Michael B.; Tuazon, Marc Cyril A.; Constantino, John Michael G. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The main purpose of this study was to determine the required number of servers of the governing queue facilities of the North and Taft Avenue Stations of Metro Rail Transit 3 (MRT3) based on the passenger flow rates at the peak hours in the morning and in the afternoon. This study determined the passenger flow rates by conducting passenger count surveys on the said MRT3 stations from 6:00 AM to 10:00 AM and from 4:00 PM to 8:00 PM. Based on the surveys, the governing queue facilities for the North Avenue Station were the guard station in the morning and the ticket booths in the afternoon while the governing queue facilities for the Taft Avenue Station were the guard station both in morning and in afternoon. The current conditions of the governing queues were simulated using discrete event simulation. Then, the number of servers was increased and then simulated. The average waiting time was computed in all the simulations and then compared with the current conditions. It was found that the required number of servers for the guard station at Taft Avenue Station in the morning and afternoon was 5 servers while the required number of servers for the ticket booths in the afternoon at North Avenue Station was 7 servers. The number of servers at the guard station in the morning at North Avenue Station was found sufficient for conditions without stop entries.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Street-railroads -- Passenger traffic; Street-railroads -- Philippines -- Manila Metropolitan Area